COMPARATIVE STUDY OF FISHING TRAPS BUSINESS BY OWN OWNERSHIP SYSTEM AND PROFIT SHARING SYSTEM IN THE BINTAN TIMUR DISTRICTS OF BINTAN REGENCY OF RIAU ISLANDS PROVINCE - Rhamadhan, Ilham; Bathara, Lamun; ', Hendrik (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was carried out on 21 March to 02 April 2016 in The BintanTimur Districts of Bintan Regency of Riau Islands Province. The methods used inthis research is a survey method. Research results show that in district of BintanTimur there are two types of businesses Fishing Traps that is sharing resultssystem and its own proprietary system. Investment on Fishing Traps systems forgreater results than ownership system of its own. Revenue sharing system fishingtraps larger than reefs bubu business ownership system of its own, for an averagerevenues – fishing traps by sharing results systems is IDR41,151,000 and themedian income for clean business personal property system fishing traps isamounting to IDR5.865.000. In order for the results system fishing traps netincome greater effort but the percentage of smaller divisions. In the businesspersonal property system fishing traps net income of smaller businesses but alarger percentage of the Division.For sustainability efforts fishing traps seen from natural resources andpotential revenues exist, can be said to be business activities can continue itsactivities fishing traps. Where business system for fishing traps results havegreater opportunities than business personal property system fishing traps.Keyword: Comparative Studies, Fishing Traps, Bintan Timur